2015
DOI: 10.1002/ccr3.201
|View full text |Cite
|
Sign up to set email alerts
|

Polyclonal hyperviscosity syndrome in IgG4‐related disease and associated conditions

Abstract: Key Clinical MessagePolyclonal hyperviscosity syndrome (HVS) is rare and has been reported in various disorders of immune dysregulation and lymphoid hyperplasia. IgG4-Related Disease (IgG4-RD) is an emerging disorder often associated with exuberant hypergammaglobulinemia, and this review of seven cases establishes IgG4-RD as an important cause of polyclonal HVS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…In fact, we previously published a case report with a diagnostic label of idiopathic HES, reviewed by several world experts in eosinophilia who concurred with the diagnosis, which was subsequently found to be IgG4-RD. 27,28 Findings of a myeloid clonal disorder such as increased blast cells, abnormal karyotype, mutations in PDGFR-alpha/beta, FGFR-1 and PCM1-JAK2 are not seen in IgG4-RD. However, differentiating lymphocytic-variant HES from IgG4-RD can be more challenging.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…In fact, we previously published a case report with a diagnostic label of idiopathic HES, reviewed by several world experts in eosinophilia who concurred with the diagnosis, which was subsequently found to be IgG4-RD. 27,28 Findings of a myeloid clonal disorder such as increased blast cells, abnormal karyotype, mutations in PDGFR-alpha/beta, FGFR-1 and PCM1-JAK2 are not seen in IgG4-RD. However, differentiating lymphocytic-variant HES from IgG4-RD can be more challenging.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Given that IgG4‐RD and L‐HES present with overlapping clinical and laboratory features such as asthma, atopy, lymphadenopathy, eosinophilia, and elevated serum immunoglobulins, differentiating between these two rare entities is an underappreciated diagnostic challenge . We previously published the case of a young woman with polyclonal hyperviscosity syndrome and eosinophilia labeled as idiopathic HES, a diagnosis confirmed prior to publication by international experts in eosinophilia (case I3 in this study); however, 2 years after publication, she was found to have histologically confirmed IgG4‐RD . Given the potential diagnostic confusion between these two entities, and the lack of large studies comparing them, we conducted a comparative case series describing the clinical and laboratory features of patients with IgG4‐RD and L‐HES.…”
Section: Introductionmentioning
confidence: 67%
“…Steroid-sparing agents such as azathioprine, mycophenolate mofetil, 6-mercaptopurine, methotrexate, tacrolimus, or cyclophosphamide have been used, mainly in the setting of AIP, with limited success [ 38 ]. Rituximab is effective in most cases refractory to steroids and other immunomodulators, although rare cases requiring more intensive therapy such as purine analogues have been reported [ 39 ]. A recent case report confirmed the effectiveness of rituximab in a steroid-refractory patient with IgG4-TIN, with sustained improvement in renal function [ 40 ].…”
Section: Main Textmentioning
confidence: 99%